Symptomatic Recovery in Miller Fisher Syndrome Parallels Vestibular–Perceptual and not Vestibular–Ocular Reflex Function - Seemungal, Barry M.; Masaoutis, Panos; Green, David; Plant, Gordon; Bronstein, Adolfo M. (Frontiers in Neurology, 2011)
Unpleasant visual symptoms including oscillopsia and dizziness may occur when there is unexpected motion of the visual world across the subject’s retina (‘retinal-slip’) as in an acute spontaneous nystagmus or on head movement with an acute ophthalmoplegia. In contrast, subjects with chronic ocular dysmotility, e.g. congenital nystagmus or CPEO (chronic progressive external ophthalmoplegia), are typically symptom free. The adaptive processes that render chronic patients asymptomatic are obscure but may include a suppression of oscillopsia perception as well as an increased tolerance to perceived oscillopsia. Such chronic asymptomatic patients display an attenuation of vestibular-mediated angular velocity perception, implying a possible contributory role in the adaptive process. In order to assess causality between symptoms, signs (i.e. eye-movements) and vestibular perceptual function, we prospectively assessed symptom ratings and ocular-motor and perceptual vestibular function, in a patient with acute but transient ophthalmoplegia due to Miller Fisher Syndrome (as a model of visuo-vestibular adaptation). The data show that perceptual measures of vestibular function display a significant attenuation as compared to ocularmotor measures during the acute, symptomatic period. Perhaps significantly, both symptomatic recovery and normalisation of vestibular perceptual function were delayed and then occurred in a parallel fashion. This is the first report showing that symptomatic recovery of visuo-vestibular symptoms is better paralleled by vestibular-perceptual testing than VOR (vestibular ocular reflex) measures. The findings may have implications for the understanding of patients with chronic vestibular symptoms where VOR testing is often unhelpful.